2008
DOI: 10.1007/s11783-008-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and chromate removal from water by iron chips—Effects of anions

Abstract: The purpose of this study is to estimate the removal efficiency of As and Cr (VI) by one kind of industrial waste -iron chips, as well as to estimate the effects of typical inorganic anions (sulfate, phosphate, and nitrate), and typical organic anions (citrate, oxalate, and humate) on As or Cr (VI) removal. The results showed that 98% of As (V) and 92% of As (III) could be removed from aqueous phase by the iron chips within 60 min. Compared with As species, Cr (VI) was removed much more rapidly and efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…− , NO 3 − and SO 4 2− ) [137][138][139]. Discrepancies among studies resulted mostly from the diversity of other operational variables like the Fe 0 intrinsic reactivity, Fe 0 dosage, the mixing rates, and experimental duration.…”
Section: The Nature Of the Electrolytementioning
confidence: 99%
“…− , NO 3 − and SO 4 2− ) [137][138][139]. Discrepancies among studies resulted mostly from the diversity of other operational variables like the Fe 0 intrinsic reactivity, Fe 0 dosage, the mixing rates, and experimental duration.…”
Section: The Nature Of the Electrolytementioning
confidence: 99%
“…Mak et al (2011) showed that removal of the co-present Cr(VI) and As(V) from humic acid-rich groundwater was more efficient with a combination of ZVI and iron oxide-coated sand (IOCS) than with ZVI or IOCS alone; this study further suggests that whilst As(V) was mainly removed by the IOCS and the iron corrosion products, Cr(VI) was mainly removed by ZVI and its corrosion products. Zhang et al (2008) reported that whilst oxalate slightly accelerated Cr(VI) removal rate, both citrate and humate retarded Cr(VI) removal. On the contrary, the results of indicate that both citric and oxalic acids accelerated Cr(VI) reduction rate by complexing the free iron cations, which prevented further passivation of ZVI ).…”
Section: Effect Of the Co-presence Of Organic Substancesmentioning
confidence: 99%
“…Scrap iron filings used by Juniapoon and Weerapong (2006) were pretreated by washing with 3% HCl at an agitating rate of 150 rpm for 30 min. Zhang et al (2008) performed Cr(VI) reduction experiments by using ZVI chips washed with 10% HCl and dried under N 2 stream. Zhou et al (2008) removed oil and oxides from the surface of ZVI powder using 0.1 M NaOH, 0.1 M HCl and deionized water, sequentially.…”
Section: Effect Of Zvi Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation